Biodiversity-Climate-Society Nexus assessment through Participatory System Dynamics Model. The case study of Amazon forest-based value chain - Santoro, Stefania; Pagano, Alessandro; Francesconi, Wendy; Mello, Denyse; Giordano, Raffaele (Elsevier, 2025)
The Biodiversity-Climate-Society (BCS) Nexus arises from the awareness of defining the integration of social, ecological and climate dimensions to address complex global challenges. The complexity related to feedback loops and combined interactions at spatial, temporal and organisational scales highlights the need for innovative and transdisciplinary analytical tools that consider local contexts, multi-scale interactions and social and political dimensions. To this aim, this study offers a methodological framework based on the Participatory System Dynamics Model (PSDM) to analyse and map the complex interaction of Nexus. The model-building process also integrates local knowledge, Ecosystem Services (ES), and value chain impacts. Using this method in Rondônia's forest-based value chain, the study shows how forest cover changes and unstainable activities threaten vital ecosystem services, especially for Indigenous communities. Through a participatory approach including local communities and stakeholders, the study generated shared knowledge and promoted dialogue to identify the main challenges toward transformative change.